2015
DOI: 10.1016/j.appet.2014.12.108
|View full text |Cite
|
Sign up to set email alerts
|

Optimal central obesity measurement site for assessing cardiometabolic and type 2 diabetes risk in middle-aged adults

Abstract: ObjectivesDespite recommendations that central obesity assessment should be employed as a marker of cardiometabolic health, no consensus exists regarding measurement protocol. This study examined a range of anthropometric variables and their relationships with cardiometabolic features and type 2 diabetes in order to ascertain whether measurement site influences discriminatory accuracy. In particular, we compared waist circumference (WC) measured at two sites: (1) immediately below the lowest rib (WC rib) and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Another potential limitation was the measurement of WC at the umbilicus in the ARIC protocol, which differs from the sites commonly use in the other epidemiologic studies (e.g. superior border of the iliac crest) . Because approximately one‐third of the US population with T2DM is undiagnosed, there may be some misclassification of individuals with T2DM in the ARIC cohort that may have biased our effect estimates towards the null.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential limitation was the measurement of WC at the umbilicus in the ARIC protocol, which differs from the sites commonly use in the other epidemiologic studies (e.g. superior border of the iliac crest) . Because approximately one‐third of the US population with T2DM is undiagnosed, there may be some misclassification of individuals with T2DM in the ARIC cohort that may have biased our effect estimates towards the null.…”
Section: Discussionmentioning
confidence: 99%
“…WHR was calculated by dividing the waist measurement by the hip measurement [8,9]. Derivation of the ROC curves was based on a method by Obuchowski [10] for continuous-scale of gold standards. ROC analyses were performed in order to evaluate the general performance of the BMI, WC and WHR.…”
Section: Area Of Study and Sample Sizementioning
confidence: 99%
“…First is that other WC measurement sites were not evaluated. Other studies have concluded that WC measurement using the lowest rib was more reproducible and easier to obtain compared to WC-WHO 2,13,14 ; hence its assessment could be clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in Ireland had similar findings, with WC measured below the lowest rib showing the strongest associations with hypertension, dyslipidemia and DM in both genders. 14 In a study by Ma et al, conducted in Taiwan, WC measurement at the iliac crest (WC-IC) and midway between the lowest rib and iliac crest (WC-mid) were compared -they found greater correlations between WCmid and VFA, blood pressure, blood glucose, hemoglobin A1c and lipid levels. 15 Identification of central obesity using WC-mid was also able to predict the development of DM after 31 months.…”
Section: Study Proceduresmentioning
confidence: 99%